The effect of persuasive messages on students' global warming opinions : a focus on source credibility. - Mahoney, Shiva (My University, 2013)
People are exposed to and influenced by persuasive tactics on a daily basis. Greater knowledge on the processes of persuasion would allow for the development of mechanisms that can assist in building people’s resistance to corrupt persuasive attempts and to heighten the use of persuasion for purposes that are beneficial. Despite the extensive amount of research that has been dedicated to investigating these dynamics, understandings remain predominantly inconclusive. It is for these reasons that this study sought to gain a greater understanding of the role of source credibility in persuasive processes. ‘Time’ and ‘source credibility’ were manipulated as the independent variables and used to assess changes in the dependent variable of ‘global warming opinions’. Results showed a general decline in global warming concern across the control and experimental conditions. These results highlighted the role of other interacting variables in persuasive contexts, while also further highlighting the great need for future studies in this domain.
Keywords: Persuasion (Psychology); Global warming--South Africa--Public opinion.; College students--South Africa--Attitudes.